Sociodemographic determinants of coping with difficult situations for nursing staff - Janusz Kirenko; Ewa Sienkiewicz; Jolanta Szymańska; Anna Malm (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The results of coping with problematic situations can be assessed by analyzing physiological responses, motor activities and emotional symptoms. The more effectively a person copes in a problematic situation, the better his/her psychosocial functioning. The adequacy of the selected coping profile affects the state of somatic and mental health. The most important feature of coping should be flexibility - adaptation to changing conditions. The aim of the study was to assess the sociodemographic factors conditioning coping with difficult situations by nursing staff. The study included an 81-member group of nurses. The original "certificate of origin" was used for the sociodemographic characteristics of the subjects studied and the Questionnaire for coping with problems (WCQ Lazarus and Folkman) was provided. The study showed that there is a relationship between dealing with difficult situations by nursing staff and the place of residence, age and professional experience. Individual strategies of coping with difficult situations by respondents do not correlate with gender and education. The respondents most often choose the coping profile described as a positive attitude. Concentration on the problem and a positive attitude have the greatest impact on the psychosocial functioning of the respondents. The skills of coping with problems in difficult situations by nursing staff are partially conditioned by sociodemographic analysis. Interpersonal skills in the field of social communication and immune resources are of great importance. It is necessary to extend the research with the determinants of personality dispositions of nursing staff in order to determine their intra-personal resources, psychosocial - sense of coherence, self-esteem and social support. Obtained information on occupational predispositions may be useful in vocational education and training of nursing staff.